2018
DOI: 10.1080/00140139.2018.1493150
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric analysis of 3D ear scans of Koreans and Caucasians for ear product design

Abstract: CCW: cavum concha width; CV: coefficient of variation; EB: ear breadth; EL: ear length; SD: standard deviation; SE: sampling error; 3D: 3 dimensional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 27 publications
3
36
0
Order By: Relevance
“…Ear growths throughout the whole lifetime were presented for Germans (Niemitz et al, 2007) and Italians (Sforza et al, 2009). When comparing populations, Alexander, Stott, Sivakumar, and Kang (2011) reported that Indians had larger ear length than Caucasians and African/Afro‐Caribbean peoples, significantly in males and not significantly in females, Lee et al (2018) found that Caucasians had wider but shorter ears than Koreans, and Hossein, Payam, and Masih (2018) determined that Hamadan men had significantly greater ear size than Caucasian men. In regard to gender differences, these investigations revealed that females have smaller ear length and width than males for Korean (Jung & Jung, 2003), Turkish (Barut & Aktunc, 2006; Tatlisumak et al, 2015), and Italian peoples (Sforza et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ear growths throughout the whole lifetime were presented for Germans (Niemitz et al, 2007) and Italians (Sforza et al, 2009). When comparing populations, Alexander, Stott, Sivakumar, and Kang (2011) reported that Indians had larger ear length than Caucasians and African/Afro‐Caribbean peoples, significantly in males and not significantly in females, Lee et al (2018) found that Caucasians had wider but shorter ears than Koreans, and Hossein, Payam, and Masih (2018) determined that Hamadan men had significantly greater ear size than Caucasian men. In regard to gender differences, these investigations revealed that females have smaller ear length and width than males for Korean (Jung & Jung, 2003), Turkish (Barut & Aktunc, 2006; Tatlisumak et al, 2015), and Italian peoples (Sforza et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, researchers have conducted ear anthropometry with 3D technologies. Different techniques have been applied to collect the external ear data, including stereophotogrammetry (Sforza et al, 2009), CT (Wang, Dong, Zhao, Bai, & Wu, 2011; Yu et al, 2015), and 3D scanning technology (Chiou et al, 2016; Ji et al, 2018; Lee et al, 2016; Lee et al, 2018; Modabber et al, 2018; Zhu, Ji, Gao, & Hu, 2017). Certain information, including specific dimensions and surface information, was extracted from 3D models for further analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations